Pengaruh Koneksi Politik, Capital Intensity, dan Corporate Social Responsibility Disclosure Terhadap Tax Avoidance - Andi Chaerunnisa Ishak; Ardan Gani Asalam (Politeknik Ganesha Medan, 2023)
Based on the central government's financial report regarding targets and realization of tax revenues for the last 4 years, it is known that in 2018 to 2020 tax realization did not reach the set targets. This shows that in that year there was a shortfall condition. Tax avoidance can be caused by several factors including political connections, capital intensity, and corporate social responsibility disclosure. The purpose of this study is to find out and explain how tax avoidance is influenced by political connections, capital intensity, and corporate social responsibility disclosure in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The research method used is the sampling technique with a descriptive approach and deductive in nature with the research strategy used is a case study. The data used in this research is 10 samples of companies with an observation period of 4 (four) years so that 40 data were used in this study. The data in this study were analyzed using a panel data regression model with the help of excel and eviews 12 software. Results research shows that political connections, capital intensity, and corporate social responsibility disclosure simultaneously affect tax avoidance. Partially, the capital intensity variable has a negative effect on tax avoidance. While political connections and corporate social responsibility disclosure has no effect on tax avoidance.